Different Effects of Premature Infant Formula and Breast Milk on Intestinal Microecological Development in Premature Infants - Chen, Cheng; Yin, Qiuyue; Wu, Hui; Cheng, Lei; Kwon, Jung-Il; Jin, Juan; Han, Tongyan; Che, Huilian (Frontiers in Microbiology, 2020)
Intestinal microecology has been shown to participate in the pathogenesis of many diseases through different pathways, and the intestinal microecology of premature infants is significantly different from full-term infants. Intestinal microecology in premature infants is affected by various factors such as gestational age, diet, antibiotic use. However, there are few studies focus on the effects of diet on intestinal microecological development in premature infants. This study explored the different effects of the formula milk (FM) and breast milk (BM) for the development of intestinal microecology in premature infants. The results showed that BM feeding increases the alpha diversity of the intestinal flora, however, FM feeding contributes to the increase in short-chain fatty acids (SCFAs) in the gut of preterm infants. The growth environment has an important influence on the β diversity of intestinal microecology, the genomic function, and the evolution of intestinal microecology in premature infants. The intestinal microecology in premature infants is significantly associated with gestational age and weight gain. This study explored the effects of feeding methods and growth environment on intestinal microecology in premature infants, and provided a basis for promoting the healthy development of premature infants.